2014
DOI: 10.1017/s0001867800006947
|View full text |Cite
|
Sign up to set email alerts
|

Random Fluid Limit of an Overloaded Polling Model

Abstract: In the present paper, we study the evolution of an overloaded cyclic polling model that starts empty. Exploiting a connection with multitype branching processes, we derive fluid asymptotics for the joint queue length process. Under passage to the fluid dynamics, the server switches between the queues infinitely many times in any finite time interval causing frequent oscillatory behavior of the fluid limit in the neighborhood of zero. Moreover, the fluid limit is random. Additionally, we suggest a method that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 16 publications
(8 reference statements)
1
25
0
Order By: Relevance
“…Remark. Remerova et al [25,Lemma 3] discuss the finiteness of E[f (B)] for the M/G/1 busy period B for a quite general class of functions f (•). They obtain bounds on moments of B that are more general but less sharp than Theorem 5.4.…”
Section: Fractional Moments Of Busy Periodsmentioning
confidence: 99%
“…Remark. Remerova et al [25,Lemma 3] discuss the finiteness of E[f (B)] for the M/G/1 busy period B for a quite general class of functions f (•). They obtain bounds on moments of B that are more general but less sharp than Theorem 5.4.…”
Section: Fractional Moments Of Busy Periodsmentioning
confidence: 99%
“…However, hardly any attention has been given to the overloaded polling system. The few literature refers to [11][12][13][14]. By using measure-valued state descriptor, Puha et al [11] proved that the overloaded GI/GI/ processor sharing queues converge in distribution to supercritical uid models and a uid limit result is proved as rst order approximations to overloaded processor sharing queues.…”
Section: Introductionmentioning
confidence: 99%
“…Using both uid and di usion limits, Jennings et al [13] showed that the virtual waiting time process of an overloaded Multi-class FIFO( rstin-rst-out) queue with abandonments converges to a limiting deterministic uid process. Instead Remerova et al [14] showed the uid asymptotic process for the joint queue length process on an overloaded branchingtype cyclic polling system by using the asymptotic properties of multi-type branching processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly unusual for such random dynamics to occur, as in queueing networks typically the random characteristics vanish and deterministic limits emerge on the fluid scale. A few exceptions are known for various polling-type models as considered in [13,21,14].…”
mentioning
confidence: 99%